iConference 2014 Proceedings 2014
DOI: 10.9776/14054
|View full text |Cite
|
Sign up to set email alerts
|

Motivations Affecting Initial and Long-Term Participation in Citizen Science Projects in Three Countries

Abstract: Reliance on volunteer participation for citizen science has become extremely popular. Cutting across disciplines, locations, and participation practices, hundreds of thousands of volunteers throughout the world are helping scientists accomplish tasks they could not otherwise perform. Although existing projects have demonstrated the value of involving volunteers in data collection, relatively few projects have been successful in maintaining volunteers' continued involvement over long periods of time. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 38 publications
8
44
1
Order By: Relevance
“…The results are similar to previous studies on environmental volunteer motivations with "helping the environment" as the strongest motivator and "advancing one's career" as the weakest motivator [Asah and Blahna, 2012;Bruyere and Rappe, 2007;Jacobson, Carlton and Monroe, 2012;King and Lynch, 1998;Roggenbuck et al, 2001;Ryan, Kaplan and Grese, 2001]. "To contribute to scientific knowledge" was the fourth strongest motivator in the present study, although this motivator was found explicitly in only one previous study on citizen science [Raddick et al, 2010] and only briefly mentioned in another [Rotman et al, 2014]. This motivator is examined more carefully below.…”
Section: Motivations To Participatecontrasting
confidence: 39%
See 2 more Smart Citations
“…The results are similar to previous studies on environmental volunteer motivations with "helping the environment" as the strongest motivator and "advancing one's career" as the weakest motivator [Asah and Blahna, 2012;Bruyere and Rappe, 2007;Jacobson, Carlton and Monroe, 2012;King and Lynch, 1998;Roggenbuck et al, 2001;Ryan, Kaplan and Grese, 2001]. "To contribute to scientific knowledge" was the fourth strongest motivator in the present study, although this motivator was found explicitly in only one previous study on citizen science [Raddick et al, 2010] and only briefly mentioned in another [Rotman et al, 2014]. This motivator is examined more carefully below.…”
Section: Motivations To Participatecontrasting
confidence: 39%
“…Volunteers felt more strongly about the results being shared with them than about the data being used for scientific publication. This reinforces claims made by other researchers that coordinators need to share results with their volunteers [Bell et al, 2008;Knoke, 1981;Nov, Arazy and Anderson, 2014;Roggenbuck et al, 2001;Rotman et al, 2014]. Further research could be done to explore the best or preferred methods for communicating results with volunteers.…”
Section: Want To Contribute To Scientific Knowledge Vs It Is Impormentioning
confidence: 63%
See 1 more Smart Citation
“…Researchers have also investigated motivations across ecological projects [Rotman et al, 2012;Rotman et al, 2014] and Zooniverse projects [Reed et al, 2013].…”
Section: Motivationsmentioning
confidence: 99%
“…-Interest in the research topic [Raddick et al, 2010;Causer and Wallace, 2012;Crowston and Prestopnik, 2013;Iacovides et al, 2013;Curtis, 2015;Eveleigh et al, 2014;Jennett et al, 2014;Reed et al, 2013] -Learning new information [Raddick et al, 2010;Crowston and Prestopnik, 2013;Nov, Arazy and Anderson, 2010;Reed et al, 2013] -Contributing to original research [Raddick et al, 2010;Raddick et al, 2013;Nov, Arazy and Anderson, 2010;Curtis, 2015;Jennett et al, 2014;Reed et al, 2013] -Enjoying the research task [Raddick et al, 2010;Crowston and Prestopnik, 2013;Nov, Arazy and Anderson, 2010;Nov, Arazy and Anderson, 2011;Curtis, 2015;Eveleigh et al, 2014;Jennett et al, 2014;Reed et al, 2013] -Sharing the same goals and values as the project [Nov, Arazy and Anderson, 2010;Nov, Arazy and Anderson, 2011;Rotman et al, 2014] -Helping others and feeling part of a team [Raddick et al, 2010;Nov, Arazy and Anderson, 2010;Nov, Arazy and Anderson, 2011;Iacovides et al, 2013;Curtis, 2015;Jennett et al, 2014;Bowser et al, 2013;Rotman et al, 2014;Reed et al, 2013] JCOM 15(03)...…”
Section: Motivationsmentioning
confidence: 99%